UNRAVELING THE PHILOSOPHICAL ANALYSIS ON RELIGIOUS VIOLENCE - Muhtadi Abdul Mun'im (Institut Dirosat Islamiyah Al-Amien Prenduan, 2024)
Religious violence has been a recurring issue throughout history, evoking deep emotions and raising profound questions about the nature of faith, humanity, and conflict. In this article, we embark on a philosophical analysis to unravel the complex dynamics behind religious violence, especially on the meaning dynamics among various contexts, its causes, and moral justification. This article uses conceptual analysis as the method which involves examining and clarifying the key concepts related to religious violence. It examines how individuals and groups use religious beliefs to justify violence and examines various case studies from different religious traditions, including Christianity, Judaism, and Islam. It provides insights into the motivations and ideologies that underlie acts of violence perpetrated in the name of God. This research provides a foundation for developing strategies to counteract and promote peaceful coexistence in diverse societies.Religious violence has been a recurring issue throughout history, evoking deep emotions and raising profound questions about the nature of faith, humanity, and conflict. In this article, we embark on a philosophical analysis to unravel the complex dynamics behind religious violence, especially on the meaning dynamics among various contexts, its causes, and moral justification. This article uses conceptual analysis as the method which involves examining and clarifying the key concepts related to religious violence. It examines how individuals and groups use religious beliefs to justify violence and examines various case studies from different religious traditions, including Christianity, Judaism, and Islam. It provides insights into the motivations and ideologies that underlie acts of violence perpetrated in the name of God. This research provides a foundation for developing strategies to counteract and promote peaceful coexistence in diverse societies.